Developing Brand Image (DeBI) dalam Membangun Citra Positif Lembaga Melalui Media Sosial - Rojabi Azharghany; Lilis Suryani; Dwi Fitrianti Arifah (GUYUB: Journal of Community Engagement, 2024)
MAS Mirqotul Ulum faces challenges in developing its institution's brand image, especially through social media. Despite having a good reputation at the local level and having adequate facilities to support the development of its brand image, the madrasah has not fully utilized digital platforms to reach a wider audience and is still unable to formulate and implement effective strategies through social media. Facilities such as computer labs and good internet access can actually be used for digital marketing and content creation activities. Based on these conditions, it is important to implement the Developing Brand Image (DeBI) Program to build a positive image of the institution through social media at MAS Mirqotul Ulum Banyuanyar Probolinggo. Through four stages consisting of needs and potential analysis, training and workshops, strategy implementation, and evaluation and monitoring, the DeBI program has provided a strong foundation for MAS Mirqotul Ulum to continue to develop in the digital era. An in-depth SWOT analysis, effective training, and a targeted implementation strategy all contribute to the program's success. With the results achieved, MAS Mirqotul Ulum now has strong capital to continue and develop its digital communication strategy in the future.